2020
DOI: 10.3390/agronomy10010128
|View full text |Cite
|
Sign up to set email alerts
|

CitrusYield: A Dashboard for Mapping Yield and Fruit Quality of Citrus in Precision Agriculture

Abstract: The application of new technologies in precision agriculture offers the possibility to link information to very specific crop locations. The spatial representation of these agricultural data through yield and fruit quality maps allows for crop management in a precise way that means that agricultural operations may be carried out considering intraorchard variability, thus resulting in greater efficiency. The aim of this work was to advance the development of new tools for the generation of yield and quality map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…Plant cover was contained under tillage and flame weeding. Respect to mowing, the vegetation underwent a major disturbance which created a difficulty in re-sprouting [25]. Under mowing, instead, where many perennial and taller plants were detected, the plants were ready and adapted for a rapid regrowth (see also discussion about functional groups).…”
Section: Effects Of Management On Plant Diversity and Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…Plant cover was contained under tillage and flame weeding. Respect to mowing, the vegetation underwent a major disturbance which created a difficulty in re-sprouting [25]. Under mowing, instead, where many perennial and taller plants were detected, the plants were ready and adapted for a rapid regrowth (see also discussion about functional groups).…”
Section: Effects Of Management On Plant Diversity and Abundancementioning
confidence: 99%
“…In particular, it was shown that type and intensity of management can produce marked changes in the biodiversity associated to the vineyard [20,24]. As an example, concerning the merely weed control, flaming was compared to glyphosate, hot foam and nonanoic acid for weed control, and it was shown that flaming and hot foam were more efficient than the other tested techniques [25]. In this work, the effect of one-sided biomass-fueled flaming at different intensities (slow and fast speed flaming) on plant community composition and abundance in the vineyard was assessed in comparison to mechanical tillage and mowing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The production of citrus is an important agricultural activity, and in Brazil it occupies a relevant position in the production of fruit, both for the fresh fruit market and to produce concentrate orange juice ( Carvalho et al, 2019 ; González-González et al, 2020 ). However, this important crop is affected by different pathogens, such as Colletotrichum abscissum , Phyllosticta citricarpa, Xanthomonas citri subsp.…”
Section: Introductionmentioning
confidence: 99%
“…In precision agriculture, maturity classification is important in phenotyping [ 14 ], and mapping yield and quality for management decisions (e.g., irrigation, fertilization [ 15 ]). Maturity is an important factor in determining the storage life and ripening quality of fruits [ 16 ] and influences the market value and choice of the consumer [ 17 ].…”
Section: Introductionmentioning
confidence: 99%